Principles of Decision Making on the Prescription of Medicines. What else Do You Need to Know when Interpreting the Results of Clinical Trials? - Yuliya A. Petrovskaya (Pediatričeskaâ Farmakologiâ, 2018)
What can become the basis for the decision making when prescribing a medicine, choosing one instead of another? Words and their combinations ‘randomised controlled study’, ‘double blind’, ‘meta-analysis’, ‘relevant difference’ have a kind of hypnotic effect on the doctor and often it is enough to make a positive impression and convince of the need to prescribe a medicine. Indeed, randomisation and a double-blind method of enrolling patients are the main ways to avoid systematic errors in research. However, this is not enough to decide what medicine to choose. When analysing the results of clinical trials, it is necessary to know a number of details that are important, sometimes critical, without regard to which it is possible to make false or incorrect conclusions about the efficacy of medicines. The article is devoted to the peculiarities of clinical trials which need to be paid no less attention than randomisation, double-blind method, and statistical significance of the obtained results.